ANALISIS GAYA BAHASA DAN VARIASI BAHASA DALAM UNGGAHAN AKUN INSTAGRAM MOOD BOOSTER KAJIAN SOSIOLINGUISTIK - Neha Tita Ardila; Tarida Ilham Manurung (STKIP Pesisir Selatan, 2026)
The study aims to describe the use of language style and language variation in posts on mood booster-themed Instagram accounts through a sociolinguistic study. This study used a qualitative descriptive method with data sources in the form of captions posted on the mood booster Instagram account. Data collection techniques were conducted through observation and documentation. Data analysis techniques were carried out by identifying, analyzing, and drawing conclusions. The results show that posts on the mood booster account often use persuasive language styles, metaphors, repetition, and hyperbole to motivate and build positive emotions in their followers. Furthermore, language variations were found in the form of non-standard language, slang, abbreviations, code-mixing between Indonesian and English, and the use of emojis to support expression in digital communication. The use of language style and language variations is influenced by communication goals, which are motivational, relaxed, and engaging with social media users, particularly teenagers and young adults. Based on the research results, it can be concluded that the use of language style and language variations in posts on the Mood Booster Instagram account serves to attract readers' attention, reinforce the message's motivation, and create a close relationship with the audience on social media.